Seek : composition portfolio and commentaries - Buckley, Linda (Trinity College (Dublin, Ireland). Department of Music, 2010)
This thesis serves as an accompanying commentary for a portfolio of ten musical compositions composed between 2005 and 2009. The works presented incorporate a broad range of forces and performance contexts, from live instrumental performer with electronics to multi-channel spatial works, string quartet to Javanese gamelan as well as bi-locational orchestral performance. A thread of compositional approach may be traced throughout the pieces, with a strong focus on the possibilities of timbre. A review of work is presented which aims to contextualize the concepts explored in the music, as well as a consideration of the individual concerns of the composer.
Keywords: Music, Ph.D.; Ph.D. Trinity College Dublin